2014
DOI: 10.1161/01.str.0000437068.30550.cf
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Decline in Stroke Mortality

Abstract: Background and Purpose Stroke mortality has been declining since the early twentieth century. The reasons for this are not completely understood, although the decline is welcome. As a result of recent striking and more accelerated decreases in stroke mortality, stroke has fallen from the third to the fourth leading cause of death in the United States. This has prompted a detailed assessment of the factors associated with this decline. This review considers the evidence of various contributors to the decline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
357
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 703 publications
(369 citation statements)
references
References 454 publications
(407 reference statements)
5
357
1
6
Order By: Relevance
“…Subset analyses also suggest that the actual values of plasma glucose and HbA1c during admission are more important than a previous documented diagnosis of diabetes per se. These data should raise concern about the risks of poor outcome after thrombolysis for patients with disorders of glucose metabolism, a condition with increasing incidence and prevalence in the United States 21. It is possible that this risk could be mitigated by better chronic and acute glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Subset analyses also suggest that the actual values of plasma glucose and HbA1c during admission are more important than a previous documented diagnosis of diabetes per se. These data should raise concern about the risks of poor outcome after thrombolysis for patients with disorders of glucose metabolism, a condition with increasing incidence and prevalence in the United States 21. It is possible that this risk could be mitigated by better chronic and acute glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of factors associated with overall decreased stroke mortality conducted after 10 years of societal experience with the JC certification program, Lackland et al. (2014) concluded that evidence is inconclusive regarding the effect of certification of stroke systems of care on mortality. Taken as a group, these findings indicate that certified status is associated with superior performance; however, it is more nearly correct that certified status tends to be earned by centers already displaying superior performance and less nearly correct that certified status conveys superior performance capability.…”
Section: Resultsmentioning
confidence: 99%
“…2011; Lackland et al. 2014). When analyzing controllable factors possibly influencing the decline in stroke mortality in Klaipeda city, these have to be assessed in the context of the whole country, since stroke risk factors in Klaipeda city have not been studied in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…2011); only in United States, it has dropped to fourth place in recent years (Lackland et al. 2014). About 29.6% of all deaths worldwide (15,616.1 million deaths) were caused by cerebrovascular diseases in 2010 (Nichols et al.…”
Section: Introductionmentioning
confidence: 99%